The role of offensive and creative priming videos in enhancing youth football players` performance during small-sided games - Coutinho, D.; Gonçalves, B.; Santos, S.; Olthof, S.; Ballester Lengua, R.; Roca, A.; Travassos, B. (Frontiers in Psychology, 2025)
Introduction: This study examined the effects of video-based priming interventions on youth football players` performance prior to playing small-sided games (SSG).